UNIT 9.27 Spinal Muscular Atrophy: Overview of Molecular Diagnostic Approaches. (1st January 2016) - Prior, Thomas W.; Nagan, Narasimhan
Abstract : Spinal muscular atrophy (SMA) is an autosomal recessive neurodegenerative disease and the most common genetic cause of infant mortality, affecting ∼1 in 10, 000 live births. The disease is characterized by progressive symmetrical muscle weakness resulting from the degeneration and loss of anterior horn cells in the spinal cord and brain stem nuclei. The disease is classified on the basis of age of onset and clinical course. SMA is caused by mutations in the telomeric copy of the survival motor neuron 1 ( SMN1 ) gene, but all patients retain a centromeric copy of the gene, SMN2 . The homozygous absence of the SMN1 exon 7 has been observed in the majority of patients and is being utilized as a reliable and sensitive SMA diagnostic test. In the majority of cases, the disease severity correlates inversely with an increased SMN2 gene copy number. Carrier detection, in the deletion cases, relies on the accurate determination of the SMN1 gene copies. Since SMA is one of the most common lethal genetic disorders, with a carrier frequency of 1 in 40 to 1 in 60, direct carrier dosage testing has been beneficial to many families. This unit attempts to highlight the molecular genetics of SMA with a focus on the advantages and limitations of the current molecular technologies. © 2016 by John Wiley & Sons, Inc.